Assessment of Willingness to Pay for Good Agricultural Practice Cabbage - CHANCHAROENCHAI, Kanokwan; SARAITHONG, Wuthiya (Journal of Environmental Management and Tourism; Vol 8 No 3 (2017): JEMT Volume VIII Issue 3(19) Summer 2017DO - 10.14505//jemt.v8.3(19).14, 2017)
This paper aims to investigate factors determining the probability of consumers’ willingness to pay a premium price for safe cabbage, as well as to estimate the mean willingness to pay a premium price for safe cabbage of consumers. Interviews with survey questionnaire are conducted in Bangkok with 540 respondents. The contingent valuation method with single- and double-bounded models is employed. The coefficients used to calculate mean willingness to pay are estimated by Maximum Likelihood method. The estimation of the change in the probability of people willing to pay for standardized cabbage is assessed by marginal effects of each factor, which are calculated by probit model. The result finds 9 significant variables as the determinants of consumers' willingness to pay. 329 respondents express their willingness to pay for GAP cabbage while 143 respondents show their true zero bids. The estimation of mean willingness to pay, therefore, is done based on these two groups of respondents. The weighted mean willingness to pay for GAP cabbage is 3.54 baht/kilogram over the current market price of normal cabbage. This amount is much lower than the difference in the variable cost between non-GAP and GAP cabbage producers, making it difficult for farmers to turn to standardized process of production.